If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -3 = 3(2 + -1y) Reorder the terms: -3 + 7y = 3(2 + -1y) -3 + 7y = (2 * 3 + -1y * 3) -3 + 7y = (6 + -3y) Solving -3 + 7y = 6 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -3 + 7y + 3y = 6 + -3y + 3y Combine like terms: 7y + 3y = 10y -3 + 10y = 6 + -3y + 3y Combine like terms: -3y + 3y = 0 -3 + 10y = 6 + 0 -3 + 10y = 6 Add '3' to each side of the equation. -3 + 3 + 10y = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 10y = 6 + 3 10y = 6 + 3 Combine like terms: 6 + 3 = 9 10y = 9 Divide each side by '10'. y = 0.9 Simplifying y = 0.9
| 6x^3+18x^2-108x=0 | | 2c-3+8=3c-8 | | 3z^2-2iz+7=0 | | x^4*x^5= | | -7x-8=-6x+14 | | -7x-8=6x+14 | | -x+6-5x=14.2x | | -5x+11=21 | | -7(-x+4)=-20-x | | 3x(x^2+5x+30)=0 | | 4y-9+y=4 | | 6x+14=4x+52 | | 0=-7y-21+x | | 3m^2+2m-16=0 | | -47+8x=9x+21 | | 4a+3c=4g | | 5p+zr=r-8f | | 3b^2+26b+35=0 | | 4x=-7/4 | | mx^2+6x+1=0 | | 1/8+1/x=1/6 | | x=2x*10 | | 34-26= | | 21y+63-3x=0 | | 55x+75x=520 | | x^3-12x^2-35x-21=0 | | 7x(6-3)+2= | | f(x)=4x^2-8x+8 | | 20x-9y=300 | | 6.3(10x)=4 | | 7x^2=-36x-5 | | 1-2x=5+6x |